Get the answers you need at Westonci.ca, where our expert community is dedicated to providing you with accurate information. Discover the answers you need from a community of experts ready to help you with their knowledge and experience in various fields. Join our platform to connect with experts ready to provide precise answers to your questions in different areas.
Sagot :
[tex](5x-3)(x^3-5x+2)=5x^4-25x^2+10x-3x^3+15x-6=\\\\
5x^4-3x^3-25x^2+25x-6\\\\
Product\ is\ equal\ to\ 5x^4-3x^3-25x^2+25x-6[/tex]
(5x-3)(x^3 - 5x +2)
Use 5x to multiply each of (x^3 - 5x +2) and -3 to multiply each of (x^3 - 5x +2)
= 5x(x^3) +5x(-5x) +5x(2) -3(x^3) -3(-5x) -3(+2).
= 5x^4 - 25x^2 + 10x - 3x^3 + 15x - 6. Rearrange and Regroup
= 5x^4 - 3x^3 - 25x^2 + 10x +15x -6.
= 5x^4 - 3x^3 - 25x^2 + 25x -6.
That's it.
Use 5x to multiply each of (x^3 - 5x +2) and -3 to multiply each of (x^3 - 5x +2)
= 5x(x^3) +5x(-5x) +5x(2) -3(x^3) -3(-5x) -3(+2).
= 5x^4 - 25x^2 + 10x - 3x^3 + 15x - 6. Rearrange and Regroup
= 5x^4 - 3x^3 - 25x^2 + 10x +15x -6.
= 5x^4 - 3x^3 - 25x^2 + 25x -6.
That's it.
Thanks for using our platform. We're always here to provide accurate and up-to-date answers to all your queries. We appreciate your visit. Our platform is always here to offer accurate and reliable answers. Return anytime. Discover more at Westonci.ca. Return for the latest expert answers and updates on various topics.